2006
DOI: 10.1016/j.neuron.2006.10.022
|View full text |Cite
|
Sign up to set email alerts
|

The Microtubule Plus-End Tracking Protein EB1 Is Required for Kv1 Voltage-Gated K+ Channel Axonal Targeting

Abstract: Axonal Kv1 channels regulate action potential propagation-an evolutionarily conserved function important for the control of motor behavior as evidenced from the linkage of human Kv1 channel mutations to myokymia/episodic ataxia type 1 (EA1) and the Shaker mutant phenotype in Drosophila. To search for the machinery that mediates axonal targeting of Kv1 channels composed of both alpha and beta subunits, we first demonstrate that Kvbeta2 is responsible for targeting Kv1 channels to the axon. Next, we show that Kv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
136
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(142 citation statements)
references
References 55 publications
(91 reference statements)
5
136
0
Order By: Relevance
“…S7) (17). In contrast, EB1 localizes in somatic puncta and along axons (15), with accumulation in the AIS for a subpopulation of neurons, as previously observed (Fig. 5C) (14).…”
Section: Ankg Binds To the End-binding Homology Domain Hydrophobicsupporting
confidence: 84%
See 1 more Smart Citation
“…S7) (17). In contrast, EB1 localizes in somatic puncta and along axons (15), with accumulation in the AIS for a subpopulation of neurons, as previously observed (Fig. 5C) (14).…”
Section: Ankg Binds To the End-binding Homology Domain Hydrophobicsupporting
confidence: 84%
“…In neurons, EB1 has been implicated in axonal transport (14,15), whereas EB3 has been characterized as a molecular link between MTs and the actin cytoskeleton (16,17). We hypothesized that EB proteins could have a role in the AIS via interaction with the ankG/βIV-spectrin scaffold.…”
mentioning
confidence: 99%
“…Previous studies identified some cargos of Kif5C, including GABA receptors (22), axonal synaptic vesicle precursors (23), APP-containing vesicles (24,25), TrkB vesicles (26), mitochondria (23,(27)(28)(29)(30)(31), AMPAR vesicles (32), and mRNA/protein complexes (33,34). Kif3 was shown to transport fodrin-associating vesicles in cultured superior cervical ganglion neurons (35), Ncadherin in the developing mouse brain (36) and axonal voltagegated potassium channel in cultured hippocampal neurons (37). Approximately 40-50% of the protein cargos identified in our proteomics analysis of three kinesin complexes are known synaptic proteins (highlighted in SI Appendix, Dataset S1).…”
Section: Discussionmentioning
confidence: 98%
“…Inhibition of microtubule growth or depletion of EB3, one of the major microtubule plusend binding proteins in mature neurons, caused the specific loss of mushroom-headed spines and increased the percentage of filopodia (Jaworski et al, 2009). Live imaging revealed that dynamic microtubules regularly depart from the dendritic shaft and enter dendritic spines (Gu et al, 2006;Hu et al, 2008;Jaworski et al, 2009) to stimulate actin polymerization and induce transient morphological changes, such as the formation of spine head protrusions or spine growth (Jaworski et al, 2009). These observations support a model in which EB3 plus-end decorated microtubules control actin dynamics and regulate spine morphology and synaptic plasticity.…”
Section: Introductionmentioning
confidence: 99%